The Role of Socioeconomic and Regulatory Factors in Industrial Digitalization: A Narrative Review - Indiworo, Rr. Hawik Ervina (Indonesian Scientific Publication, 2024)
This narrative review investigates the multi-dimensional nature of digital transformation in industrial sectors, focusing on regulatory policies, socioeconomic conditions, and technological innovations. The study aims to analyze the enabling and limiting factors that influence digitalization processes in both advanced and developing economies. Literature was gathered from Scopus, PubMed, and Google Scholar using keywords such as